Diagnostic Accuracy and Safety of Coaxial System in Oncology Patients Treated in a Specialist Cancer Center With Prospective Validation Within Clinical Trial Data - Khan, Khurum; Gonzalez-Exposito, Reyes; Cunningham, David; Koh, Dow-Mu; Woolston, Andrew; Barber, Louise; Griffiths, Beatrice; Kouvelakis, Kyriakos; Calamai, Vanessa; Bali, Monia; Khan, Nasir; Bryant, Annette; et al. (Frontiers in Oncology, 2020)
Background Image-guided tissue biopsies are critically important in the diagnosis and management of cancer patients. High-yield samples are also vital for biomarker and resistance mechanism discovery through molecular/genomic analyses. Patients and Methods All consecutive patients who underwent plugged image-guided biopsy at Royal Marsden from June 2013 until September 2016 were included in the analysis. In the next step, a second cohort of patients prospectively treated within two clinical trials (PROSPECT-C and PROSPECT-R) were assessed for the DNA yield from biopsies assessed for complex genomic analysis. Results A total of 522 plugged core biopsies were performed in 457 patients [men, 52%; median age, 63 years (range, 17–93)]. Histological diagnosis was achieved in 501 of 522 (96%) performed biopsies. Age, gender, modality, metastatic site, and seniority of the interventionist were not found to be significant factors associated with odds of failure on a logistic regression. Seventeen (3.3%) were admitted due to biopsy-related complications; nine, three, two, one, one, and one were admitted for grade I/II pain control, sepsis, vasovagal syncope, thrombosis, hematuria, and deranged liver functions, respectively; two patients with right upper quadrant pain after liver biopsy were found to have radiologically confirmed subcapsular hematoma requiring conservative treatment. One patient (0.2%) developed grade III hemorrhage following biopsy of a gastric gastrointestinal stromal tumor (GIST). Overall molecular analysis was successful in 89% (197/222 biopsies). Prospective validation in 62 biopsies gave success rates of 92.06 and 79.03% for DNA extraction of >1 μm and tmour content of >20%, respectively. Conclusion The probability of diagnostic success for complex molecular analysis is increased with plugged large coaxial needle biopsy technique, which also minimizes complications and reduces hospital stay. High-yield DNA acquisition allows genomic molecular characterization for personalized medicine.